A Contribution to the Scarabaeoid Beetles (Coleoptera: Scarabaeoidea) in Forest Nurseries of the Western Black Sea Region of Türkiye - Nuray Öztürk; Beşir Yüksel; İsmail Baysal; Marco Dellacasa (Forestist)
A survey of Scarabaeoidea species was carried out in forest nurseries of the Western Black Sea region. Seven forest nurseries in five provinces were sampled between 2021 and 2022 using forceps, pitfall trap, sweep net, light trap, and pheromone trap. In total, 3 families, 8 subfamilies, 23 genera, and 24 species were identified in this study. The antennal sensilla and aedeagus of some scarab beetles were photographed using a scanning electron microscope (SEM) and stereo micro scope. Results of Shannon–Wiener and Simpson diversity indices showed that the highest species diversity was recorded in Muzaffer Büyükterzi and Bolu Forest Nurseries with 2.254 and 1.985 respectively. Margalef’s richness index was found to be the highest in Muzaffer Büyükterzi Forest Nursery (3.620). The nursery with the highest dominance was found to be Pınar Forest Nursery with 0.351. Shannon and Simpson evenness results showed that Muzaffer Büyükterzi and Gölköy Forest Nurseries had the highest evenness with 0.907 and 0.156, respectively, while Pınar and Bolu Forest Nurseries had the lowest evenness with 0.475 and 0.081, respectively. At the end of the study, four insect species were new records for the region.